Diseño de propuestas constructivas Soil Nailing para estabilidad de taludes en sitios de la Red Nacional de Telecomunicaciones del ICE - Campos-Vallejo, Juan Carlos (Instituto Tecnológico de Costa Rica, 2017)
This document contains information about the design of constructive proposals stabilization of slopes and hillsides sites of the Red Nacional de Telecomunicaciones in the Instituto Costarricense de Electricidad (ICE), through systems implementation of type passive anchors Soil Nailing and some recommendations of erosion control geogrid, shotcrete walls against scour and channeling runoff water. For implementation of this project they have conducted studies of inspection and identification of the problem, topography studies, analysis of soil studies, and development of stability analysis models using the Slide program and construction drawings with specifications. As a result from the identification of problems they have been implemented engineering designs protection by systems of Soil Nailing, supported by the considerations Design Manual of Soil Nail Walls by Federal Highway Administration (FHWA) and other codes like, Código de Cimentaciones de Costa Rica, the Código Geotécnico de Taludes y Laderas de Costa Rica, the Código Sísmico de Costa Rica 2010, Requirements for Structural Concrete ACI-318SUS-14, and others. From the development of this document it can be concluded that it is necessary the constant maintenance of land sites foundation of ICE to continue providing telecommunication services to the population involved, reason why engineering intervention is performed.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Estudio; Geotécnico; Análisis; Propuestas; Mecánica de Suelos; Ingeniería